Chemical characteristics of bio-oil from beech wood pyrolysis separated by fractional condensation and water extraction. (December 2021) - Xu, J.; Brodu, N.; Wang, J.; Abdelouahed, L.; Taouk, B.
Abstract: The combination of two environmentally friendly methods was successfully performed to separate target chemicals from the beech wood pyrolytic bio-oil. Firstly, the fractional condensation pyrolysis oil was carried out using a system with three condensers. The effect of the temperature of the first and second condenser was studied. Water extraction was realized to further the separation of products from different condensers. Each chemical compound of the bio-oil products was identified and quantified using GC-MS and GC-FID. Distribution ratios of the target chemicals were calculated. Water and carboxylic acids were mainly recovered in the second and third condensers, whereas phenolics and sugar were mainly found in the first condenser. An increase in the first condenser temperature promoted the selectivity for phenolic and sugar compounds. Separation by water allowed recovering sugars in the water-soluble fraction, whereas phenolics remain in the water-insoluble fraction. Polarity, boiling point and water solubility of chemicals appear as key factors for process optimization. Highlights: The combination of the fractional condensation and water extraction method was built. The high temperature condenser promotes the recovery of sugar and phenol. Sugars and carboxylic acids are mainly recovered in the water-soluble fraction. Phenolic compounds are predominant in the water-insoluble fraction. Dew point and water solubility are the main parameters for the separation.